A comprehensive review on host plant resistance of wonder crop, soybean (Glycine max) against whitefly (Bemisia tabaci): A COMPREHENSIVE REVIEW ON HOST PLANT RESISTANCE OF SOYBEAN AGAINST WHITEFLY - PRIYANSHU PAWAR; ARCHANA ANOKHE; ABHISHEK SHUKLA; P DURAIMURUGAN; POOJA KUMARI; JARPLA MOUNIKA (Journal of Oilseeds Research, 2024)
Whiteflies are significant pests that adversely affect soybean yield qualitatively and quantitatively. Understanding the host plant resistance traits of soybean against whiteflies is crucial for developing resistant cultivars for sustainable management of whitefly. This review provides an overview of the defensive proteins, secondary metabolites, signalling molecules, and antioxidant systems involved in soybean's resistance mechanisms. Additionally, it discusses the genetic and molecular basis of resistance, breeding strategies, and the influence of environmental and agronomic factors.